2021
DOI: 10.31661/gmj.v10i0.2270
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Treatment with P53 Overexpression and Interferon γ Exerts a Dramatic Increase in Apoptosis Induction of U87 Cells

Abstract: Background: Gliomas possess low immunogenicity, which is an inevitable hinder in front of cancer immunotherapy. Different interferons (IFNs) may proceed apoptosis instead in p53-dependent or independent pathways. P53 induces the anti-inflammatory programmed cell death in cancer cells; on the other hand, IFN gamma (IFNγ) is a modulatory/pro-inflammatory cytokine. There are contradictory reports of whether this cytokine can possess an anti- or pro-cancerous impact on tumors. Hence, we aimed to investigate the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Our results answered some parts of this question, as we can see, the apoptosis rate induced in the U87 cells after ELF-EMF exposure is much more than in the U251 cells. It is shown that overexpression of P53 in the U87 cell line after exposure may be the main reason for apoptosis induction by radiation 51 , 52 , as in the U251 cell line, P53 is mutated it is not out mind to expect that the underlying and P53 -dependent pathways which may result in apoptosis after treatment, do not function correctly 13 . The results obtained for the MCF-7 (with wild type P53) or U251-P53 (U251 cells that received vector overexpressing P53 ) also confirmed the role of this gene in the apoptosis induction by ELF-EMF in GBM cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results answered some parts of this question, as we can see, the apoptosis rate induced in the U87 cells after ELF-EMF exposure is much more than in the U251 cells. It is shown that overexpression of P53 in the U87 cell line after exposure may be the main reason for apoptosis induction by radiation 51 , 52 , as in the U251 cell line, P53 is mutated it is not out mind to expect that the underlying and P53 -dependent pathways which may result in apoptosis after treatment, do not function correctly 13 . The results obtained for the MCF-7 (with wild type P53) or U251-P53 (U251 cells that received vector overexpressing P53 ) also confirmed the role of this gene in the apoptosis induction by ELF-EMF in GBM cells.…”
Section: Discussionmentioning
confidence: 99%
“…To assess the P53 role in apoptosis induction by ELF-EMF, pCMV-Neo-Bam-H1-p53 plasmid was used. This plasmid was kindly provided by Dr. Michael Resnick (NIEHS, NIH), by the aid of BamHI restriction enzyme and cloning, cDNA of P53 was inserted into the pCMV-NeoBam vector from Addgene (Cambridge, Massachusetts, USA) (reference 13 shows the vector map). U251 cells were transfected with 100 ng/μl concentration of this plasmid (abbreviated as U251-P53), by Lipofectamine®2000.…”
Section: Methodsmentioning
confidence: 99%
“…Due to the rapidly evolving nature of GBM and the high risk of resistance to new drugs, the development of new drugs is not considered efficient [6,7]. Therefore, identifying new applications for existing drugs with known pharmacokinetics and safety characteristics has gained a lot of interest [8,9]. One previously used drug with a good efficacy profile is dimethyl fumarate (DMF).…”
Section: Introductionmentioning
confidence: 99%